2013
DOI: 10.1182/blood-2013-03-492363
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis E virus: an underestimated opportunistic pathogen in recipients of allogeneic hematopoietic stem cell transplantation

Abstract: Key Points• The incidence of acute HEV infection after alloHSCT is relatively low, in contrast to a high probability of developing chronic hepatitis.• HEV infection or reactivation should be included in the differential diagnosis of liver enzyme abnormalities in alloHSCT recipients.Hepatitis E virus (HEV) is increasingly acknowledged as a cause of hepatitis in healthy individuals as well as immunocompromised patients. Little is known of HEV infection in recipients of allogeneic hematopoietic stem cell transpla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
111
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(126 citation statements)
references
References 26 publications
8
111
7
Order By: Relevance
“…1 Versluis et al 2 recently studied the incidence and course of HEV-infection in a large cohort of patients undergoing allogeneic hematopoietic SCT (HSCT). In contrast to previously published studies from our group 3 and others, 4 they identified a considerable number of patients with chronic HEV infection with a significant lethality.…”
mentioning
confidence: 99%
“…1 Versluis et al 2 recently studied the incidence and course of HEV-infection in a large cohort of patients undergoing allogeneic hematopoietic SCT (HSCT). In contrast to previously published studies from our group 3 and others, 4 they identified a considerable number of patients with chronic HEV infection with a significant lethality.…”
mentioning
confidence: 99%
“…Since no animal model for chronic HEV infection is available, we examined the infectivity of HEV gt3 samples of different clinical origins in the humanized liver urokinase-type plasminogen activator (uPA) transgenic mouse model on a severely immunodeficient NOD/Shi-scid/IL-2R␥ null background (uPA-NOG) and compared this to the established adenocarcinoma human alveolar basal epithelial cells (A549) culture system (19)(20)(21)(22). We demonstrate that in vitro infectivity differences of feces-, liver-, and plasma-derived HEV are paralleled in vivo.…”
mentioning
confidence: 99%
“…In both studies, ongoing HEV infection was absent. Prior to allogeneic stem cell transplantation, Versluis et al recently reported an anti-HEV IgG prevalence of 13% (287). HEV RNA was found in 8 of 328 stem cell transplant patients (2.4%) (287), and 5 patients developed chronic hepatitis (287).…”
Section: Chronic Hev Infection In Hematological Patientsmentioning
confidence: 99%
“…Case reports of chronic HEV infection in hematological patients include a patient with myeloma who required a stem cell transplant (284), a child with HEV-associated cirrhosis following bone marrow transplantation (288), and a case of HEV reactivation in a patient with acute lymphoblastic leukemia after allogeneic stem cell transplantation (289). Very recently, another case of HEV reactivation was suspected in a hematological patient (287), but no HEV reactivation was seen in a study from France (286). There are still some unresolved questions in the setting of stem cell transplantation, i.e., should all patients undergoing stem cell transplantation be screened for HEV RNA, especially if liver enzyme levels are increased?…”
Section: Chronic Hev Infection In Hematological Patientsmentioning
confidence: 99%
See 1 more Smart Citation